Studies of gauge boson pair production and trilinear couplings - Abachi, S; Abbott, B; Abolins, M; Acharya, B; Adam, I; Adams, D; Adams, M; Ahn, S; Aihara, H; Alves, G; Amidi, E; Amos, N; et al. (1997)
The gauge boson pair production processes Wγ, WW, WZ, and Zγ were studied using pp̄ collisions corresponding to an integrated luminosity of approximately 14 pb-1 at a center-of-mass energy of √s=1.8 TeV. Analysis of Wγ production with subsequent W boson decay to ℓν, (ℓ=e,μ) is reported, including a fit the pT spectrum of the photons which leads to limits on anomalous WWγ couplings. A search for WW production with subsequent decay to ℓℓ̄νν̄ (ℓ=e,μ) is presented, leading to an upper limit on the WW in WW and WZ production is described, where one W boson decays to an electron and a neutrino and the second W boson or the Z boson decays to two jets. A maximum likelihood fit to the pT spectrum fo W bosons resulted in limits on anomalous WWγ and WWZ couplings. A combined fit to the three data sets which provided the tightest limits on anomalous WWγ and WWZ couplings is also described. Limits on anomalous ZZγ and Zγγ couplings are presented from an analysis of the photon ET spectrum in Zγ events in the decay channels (ee, μμ, and νν) of the Z boson.